Evaluation of Temporomandibular Joint After Orthognathic Surgery with First Orthognathic Surgery Method: Scoping Review - Faizah, Azra Zhafirah; Yuza, Abel Tasman; Hadikrishna, Indra (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction: Dentoskeletal anomalies are defined as aberrations of the maxillofacial complex that negatively impact the dental and skeletal relation. Orthognathic surgery is a treatment option to rehabilitate dentoskeletal anomalies. Surgery first orthognathic is one of the orthognathic surgeries conducted prior to the orthodontic treatment. One of the problems that might occur following the surgery first orthognathic is related to temporomandibular joint disorder (TMD). This study aimed to map the published articles about the clinical evaluation of temporomandibular joint post-surgery first orthognathic. This study used the scoping review method, following the PRISMA-ScR guideline. The search engines utilized in this study were PubMed, ScienceDirect, and Scopus, using keywords as follows, ((surgery first orthognathic) OR (surgery first orthognathic approach)) AND (temporomandibular joint). Review: A total of eight articles suit the inclusion criteria. 119 patients underwent orthognathic surgery using the surgery first orthognathic method. Post-surgery, 25.2% of patients experienced TMD improvement, 70.6% experienced no change in the normal temporomandibular joint, and 4.2% experienced TMD impairment worse than before the surgery. Conclusion: Based on the analysis results of the studies, it can be concluded that surgery first orthognathic inclines to preserve the normal condition of the patient’s temporomandibular joint before the surgery. In some cases, surgery first orthognathic yielded opportunities to relieve the TMD symptoms. However, there is a slight risk following the surgery first orthognathic, i.e., worsening of the TMD and generating new onset of TMD.